Specialist perioperative allergy clinic services in the UK 2016: Results from the Royal College of Anaesthetists Sixth National Audit Project. Issue 10 (7th September 2017) - Egner, W.; Cook, T.; Harper, N.; Garcez, T.; Marinho, S.; Kong, K. L.; Nasser, S.; Thomas, M.; Warner, A.; Hitchman, J.; Floss, K.; ,
Summary: Background: Guidelines for investigation of perioperative drug allergy exist, but the quality of services is unknown. Specialist perioperative anaphylaxis services were surveyed through the Royal College of Anaesthetists 6 th National Audit Project. Objectives: We compare self‐declared UK practice in specialist perioperative allergy services with national recommendations. Methods: A SurveyMonkey™ questionnaire was distributed to providers of allergy services in the UK. Responses were assessed for adherence to the best practice recommendations of the British Society for Allergy and Clinical Immunology (BSACI), the Association of Anaesthetists of Great Britain and Ireland and the National Institute for Health and Care Excellence (NICE) Guidance on Drug Allergy—CG183. Results: Over 1200 patients were evaluated in 44 centres annually. Variation in workload, waiting times, access, staffing and diagnostic approach was noted. Paediatric centres had the longest routine waiting times (most wait >13 weeks) in contrast to adult centres (most wait <12 weeks). Service leads are allergists/immunologists (91%) or anaesthetists (7%). Potentially important differences were seen in: testing repertoire [10/44 (23%) lacked BSACI compliant neuromuscular blocking agent (NMBA) panels and 17/44 (39%) lacked a NAP6‐defined extended panel; many failed to screen all cases for chlorhexidine 19/44 (43%) or latex 21/44 (48%)], staffing [only 26/44 (59%) had specialist nurses and 18/44 (41%) an anaesthetist] and provision of information [18/44 (41%) gave immediate information in clinic and 5/44 (11%) sign‐posted support groups]. Most centres were able to provide diagnostic challenges to antibiotics [40/44 (91%]) and local anaesthetics [41/44 (93%)]. Conclusions and Clinical Relevance: Diagnostic testing is not harmonized, with marked variability in the NMBA panels used to identify safe alternatives. Chlorhexidine and latex are not part of routine testing in many centres. Poor access to services and patient information provision require attention. Harmonization of diagnostic approach is desirable, particularly with regard to a minimum NMBA panel for identification of safe alternatives.